2009
DOI: 10.1097/ico.0b013e31816b6a0b
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Acanthamoeba Keratitis After Orthokeratology

Abstract: Acanthamoeba keratitis can simultaneously affect both eyes during overnight orthokeratology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Bilateral AK is relatively rare with only a few reported cases in the literature all noting associated CL use. [17][18][19][20][21][22][23][24] Most case reports of bilateral AK were associated with soft CL use with the largest case series involving bilateral AK in five patients in the USA, 19 however, one case has been previously reported involving rigid gas permeable CLs. 25 Although the risk of AK may be higher with certain types of CLs such as first generation silicone hydrogel CLs, 26 CLs of any sort constitute a significant risk factor for AK and include cosmetic and orthokeratology CLs [27][28][29][30] as evidenced by the single case of cosmetic-CL related AK noted in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral AK is relatively rare with only a few reported cases in the literature all noting associated CL use. [17][18][19][20][21][22][23][24] Most case reports of bilateral AK were associated with soft CL use with the largest case series involving bilateral AK in five patients in the USA, 19 however, one case has been previously reported involving rigid gas permeable CLs. 25 Although the risk of AK may be higher with certain types of CLs such as first generation silicone hydrogel CLs, 26 CLs of any sort constitute a significant risk factor for AK and include cosmetic and orthokeratology CLs [27][28][29][30] as evidenced by the single case of cosmetic-CL related AK noted in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, paromomycin sulfate (inhibitor of the initiation and elongation steps of protein synthesis) has been shown to exhibit amoebistatic, amoebicidal, and cysticidal properties at more than 100 g per ml (33,40,54). Tobramycin (inhibitor of protein synthesis by binding to ribosomes and preventing mRNA translation, leading to cell death) has shown amoebicidal properties at more than 250 g per ml (25,80).…”
Section: Protein Synthesis-inhibiting Drugsmentioning
confidence: 99%
“…Until recently, not much had been reported of incidence or prevalence of ocular complications or ocular surface integrity associated with OOK, except for case reports of Pseudomonas aeruginosa and Acanthamoeba infections associated with this treatment. [1][2][3][4][5][6][7][8][9] Recent studies that compared OOK lens wearers to both nonlens wearers and 30-day continuous-wear silicone hydrogel lens wearers reported that, after 12 months, the greatest increases in tear film concentrations of inflammatory mediators (IL-6, IL-8, matrix metalloproteinase-9 [MMP-9], and epidermal growth factor) were in the OOK group. 10,11 Of most interest is MMP-9, which is believed to be responsible for the desquamation of differentiated apical corneal epithelial cells that express the tight junction protein, occludin.…”
mentioning
confidence: 99%